2006
DOI: 10.1002/bip.20531
|View full text |Cite
|
Sign up to set email alerts
|

Solution scattering studies of conformation stability of xylanase XYNII from Trichoderma longibrachiatum

Abstract: Xylanase (endo-1,4-beta-xylanase; EC 3.2.1.8) is an enzyme that catalyzes the hydrolysis reaction of xylan. The structure of the xylanase II (XYNII) molecule from Trichoderma longibrachoatum (formerly Trichoderma reesei) in a solution and at different pH values has been studied by small- and wide-angle scattering of synchrotron radiation (SAXS-WAXS). Analysis of the radius of gyration that characterizes xylanase has confirmed the stability of the above enzyme structure (the radius of gyration varied from 1.65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…The stability of the xylanase molecule shape in solution at 158C and in wide range of pH values (3-10) was studied in Ref. 15, where it was found that it remained relatively unchanged and similar to that implied by the crystal structure. The model of the XYNII molecule obtained from the SAXS data collected at 308C and presented in Figure 4a has also a shape similar to that implied by the crystal structure and that earlier proposed for xylanase in solution.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The stability of the xylanase molecule shape in solution at 158C and in wide range of pH values (3-10) was studied in Ref. 15, where it was found that it remained relatively unchanged and similar to that implied by the crystal structure. The model of the XYNII molecule obtained from the SAXS data collected at 308C and presented in Figure 4a has also a shape similar to that implied by the crystal structure and that earlier proposed for xylanase in solution.…”
Section: Resultsmentioning
confidence: 91%
“…This value is close to that obtained in our earlier study of native xylanase XYNII in solution (pH 6.0). 15,35 At 508C, so at the temperature optimum for enzymatic activity of xylanase XYNII, 22 the shape of the function p(r) slightly changes, which can suggest a possible change in the conformation of the xylanase molecule. Conformational changes and open-close movements of XYNII active site have been previously suggested on the basis of the X-ray crystallographic and molecular dynamic studies.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The β-jelly-roll fold is better conserved than its sequence and it can hold several functions. Such structure makes GH11 xylanases be a dense globular proteins, whose gyration radius is nearly closed to 17 Å [20]. It may be one of the reasons for GH11 xylanases be the smallest which is similar to a monomeric enzyme.…”
Section: High-level Structure Analysis Of the Xynbmentioning
confidence: 98%